A guerra submarina na costa sergipana (1942-1945) - Lina Maria Brandão de Aras (Navigator, 2012)
Among the german submarines that acted on the coast of Brazil, the performance of the U-507 was the most emblematic for the brazilians, because in addition to sink seven vessels in the South Atlantic and kill more than 600 people, it revealed the coming of the World War II to Brazil. Studying the aggressions of U-boats under the social prism was a methodological strategy to identify as the Battle of the Atlantic was built, thought and interpreted in Sergipe, from 1942 to 1945.